Tipe Hunian Gua dan Ceruk Arkeologis Masa Prasejarah di Kecamatan Tanjungsari, Gunungkidul (Sebuah Analisis Pendahuluan) - Taufiqurrahman Setiawan (Balai Arkeologi Sumatera Utara, 2008)
AbstractThe prehistoric hunter and gatherers have two type of cave or rock-shelter settlement. The first one is homebase, which they stay here for a long time and gather their food from environtment natural sources. When their environment sources empty, they hunt or gather in the other natural sources. They need other cave or rock-shelter as transit-site, make energy efficiency for a good hunting strategy trap.